2019
DOI: 10.18092/ulikidince.418132
|View full text |Cite
|
Sign up to set email alerts
|

Causality Relationship Between Foreign Direct Investment and Tourism

Abstract: This paper applies panel data regression model to investigate the relationship between foreign direct investment (FDI) and tourism in 113 countries during the period 1995-2015. Besides this, the paper attempts to research the potential causal relationship and cointegration between tourism industry and FDI while controlling for indicators such as consumption, trade openness and human capital. The obtained results indicate a significant positive impact of tourism on FDI. Moreover, three control variables are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
2
13
1
1
Order By: Relevance
“…The present study provides primary, empirical evidence of the tourism-FDI nexus. While some contemporary studies (Satrovic and Muslija, 2018;Tomohara, 2016;Yazdi et al, 2017) support the general notion of the tourism-FDI nexus, it, however, appears as though the present study is one of the first to do so across a 'deconstructed' FDI spectrum of market-, resource-, efficiency-and strategic asset-seeking FDI. In the absence of comprehensive studies that have examined all four tourism typologies collectively, the present study makes a significant contribution, albeit limited to Zimbabwe of the potential influence of tourism on FDI.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The present study provides primary, empirical evidence of the tourism-FDI nexus. While some contemporary studies (Satrovic and Muslija, 2018;Tomohara, 2016;Yazdi et al, 2017) support the general notion of the tourism-FDI nexus, it, however, appears as though the present study is one of the first to do so across a 'deconstructed' FDI spectrum of market-, resource-, efficiency-and strategic asset-seeking FDI. In the absence of comprehensive studies that have examined all four tourism typologies collectively, the present study makes a significant contribution, albeit limited to Zimbabwe of the potential influence of tourism on FDI.…”
Section: Discussioncontrasting
confidence: 54%
“…In the case of Hong Kong–China, the ability of the country to sustain its 10.4% growth rate between 2000 and 2014 is attributed to strategic investment in the country’s tourism-oriented infrastructure that included air, and maritime platforms, as well as man-made attractions such as Hong Kong Disneyland (Prideaux and Tse, 2015). Interestingly, a positive causal relationship was established between inbound tourism and FDI in the cases of top tourism destinations including France, Germany, Spain and Italy (Arain et al, 2020), whereas other studies have determined a unidirectional relationship (reverse causal relationship) within the tourism-FDI nexus in the cases of China (Tang et al, 2007), India (Selvanathan et al, 2012) and 113 other countries including the African nations of Algeria, Cameroon, the Congo, Egypt and Zimbabwe (Satrovic and Muslija, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings also confirmed the presence of one-way causality from FDI and tourism price to tourism in both short and long run. Satrovic and Muslija (2018) investigated the foreign direct investment and tourism's association in 113 countries using GMM estimates from 1995 to 2015. The results confirmed that FDI has significant direct impact on tourism, while tourism causes FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generalized method of moments Dynamic will be incorporated into the model by formalizing model equation as AR (1) model as following (Eq. 1) (Satrovic and Muslija, 2018: − error term while denotes intercept that is period specific.…”
Section: Methodsmentioning
confidence: 99%